"Let’s work out” : a study of sports participation in Singapore - Foo, Qiren (2015)
The motivating factors behind sports participation and its implications upon a community have been widely researched and debated by academics over the past decades. This paper aims to critically analyze the various driving forces and implications of sports participation in the context of Singapore and see how sports have being utilized as a social institution, as well as shaped by the various institutions surrounding it, in promoting communal spirit and social bonding amongst Singaporeans and helping to achieve the maintenance of social order through the functionalist approach. My analysis focuses on how the four basic social needs required for a society to operate efficiently are being fulfilled by sports participation in Singapore. This will help us better understand the sporting culture of Singapore and the factors motivating Singaporeans to participate in sports in today’s society.